A good neighbour : Exhibition 15th Istanbul Biennial. - Istanbul Biennial Istanbul 2017; Elmgreen & Dragset; Wilson-Goldie, Kaelen; Örer, Bige (Istanbul : Istanbul Foundation for Culture and Arts, 2017)
Abdessemed, Adel ; Akunyili rosby, Njideka ; Almanza Pereda, Alejandro ; Y. Amin, Heba ; Aslan, volkan ; Aydin, Alper ; Bingol, Burcak ; Bonvicini, Monica ; Bourgeois, Louise ; De Bruyckere, Berlinde ; et al.
Istanbul Biennial, Istanbul, 16.09.17 - 12.11.17
kunstcatalogus
Keywords: Istanbul